2023
DOI: 10.5114/wiitm.2023.128910
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental disorders in patients with pathological obesity selected for bariatric surgery in the KOS-BAR nationwide multi-centre pilot programme - a preliminary report.

Abstract: Obesity affects over 600,000 people in Poland, and bariatric surgery is a vital part of the multidisciplinary approach to treatment. To improve outcomes, Poland’s public health institutions implemented the KOS-BAR programme, a multicentre nationwide pilot initiative that includes psychiatric evaluations of patients. The aim of this study was to assess the prevalence of mental disorders, verify diagnoses, and evaluate pharmacotherapy efficacy for patients under psychiatric treatment and selected for bariatric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Other studies indicated up to 5 times higher frequency of preoperative psychiatric treatment [ 4 , 25 , 30 ]. Also, Polish preliminary data on the prevalence of mental disorders in patients qualified for the nationwide multi-center pilot of bariatric obesity treatment program (KOS-BAR) showed that 12.1% patients were in psychiatric treatment but there were additional 11.7% with de novo diagnosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicated up to 5 times higher frequency of preoperative psychiatric treatment [ 4 , 25 , 30 ]. Also, Polish preliminary data on the prevalence of mental disorders in patients qualified for the nationwide multi-center pilot of bariatric obesity treatment program (KOS-BAR) showed that 12.1% patients were in psychiatric treatment but there were additional 11.7% with de novo diagnosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%